Advanced materials and processing technologies. II, 3rd International Conference on Material Sciences and Nanomaterials (ICMSN 2019), and 3rd International Conference on Advanced Manufacturing and Materials (ICAMM 2019) - Zhao, Yuyuan (Materials science forum ;, 2020)
3rd International Conference on Materials Sciences and Nanomaterials (ICMSN 2019) and 3rd International Conference on Advanced Manufacturing and Materials (ICAMM 2019).